Comparison of phytosterol intake from FFQ with repeated 24-h dietary recalls of the Adventist Health Study-2 calibration sub-study. Issue 12 (28th June 2019) - Sirirat, Rawiwan; Heskey, Celine; Haddad, Ella; Tantamango-Bartley, Yessenia; Fraser, Gary; Mashchak, Andrew; Jaceldo-Siegl, Karen
Abstract: We evaluated the performance of an FFQ in estimating phytosterol intake against multiple 24-h dietary recalls (24HDR) using data from 1011 participants of the calibration sub-study of the Adventist Health Study-2 (AHS-2) cohort. Dietary assessments of phytosterol intake included a self-administered FFQ and six 24HDR and plasma sterols. Plasma sterols were determined using the GLC flame ionisation method. Validation of energy-adjusted phytosterol intake from the FFQ with 24HDR was conducted by calculating crude, unadjusted, partial and de-attenuated correlation coefficients ( r ) and cross-classification by race. On average, total phytosterol intake from the FFQ was 439·6 mg/d in blacks and 417·9 mg/d in whites. From the 24HDR, these were 295·6 mg/d in blacks and 351·4 mg/d in whites. Intake estimates of β-sitosterol, stigmasterol, other plant sterols and total phytosterols from the FFQ had moderate to strong correlations with estimates from 24HDR ( r  0·41–0·73). Correlations were slightly higher in whites ( r 0·42–0·73) than in blacks ( r  0·41–0·67). FFQ estimates were poorly correlated with plasma sterols as well as 24HDR v . plasma sterols. We conclude that the AHS-2 FFQ provided reasonable estimates of phytosterol intake and may be used in future studies relating phytosterol intake and disease outcomes.